2012
DOI: 10.1186/1471-2415-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Frequency doubling technology, optical coherence technology and pattern electroretinogram in ocular hypertension

Abstract: BackgroundTo assess which of three methods, namely, optical coherence tomography (OCT), pattern electroretinogram (PERG) or frequency-doubling technology (FDT), is the most sensitive and specific for detecting early glaucomatous damage in ocular hypertension (OH).MethodsFifty-two patients with OH (24 men and 28 women, mean age of 56 ± 9.6 years) with an intraocular pressure (IOP) > 21 mmHg and fifty-two control patients (25 men and 27 women, mean age of 54.8 ± 10.4 years) with IOP < 21 mmHg, were assessed. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“… 24 , 26 This compares with AUCs of 0.78 to 1.00 in the wider literature of visual field tests. 21 23 , 27 29 Expanding to nonvisual field–based glaucoma screening methods, the AUC for distinguishing glaucoma versus health controls is in the 0.70 to 0.95 range. 14 , 22 , 25 , 30 33 …”
Section: Discussionmentioning
confidence: 99%
“… 24 , 26 This compares with AUCs of 0.78 to 1.00 in the wider literature of visual field tests. 21 23 , 27 29 Expanding to nonvisual field–based glaucoma screening methods, the AUC for distinguishing glaucoma versus health controls is in the 0.70 to 0.95 range. 14 , 22 , 25 , 30 33 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in previous studies, FDT-PSD proved to be very sensitive in highlighting early damage of M-Y ganglion cells in diseases that alter the visual pathway (eg, ocular hypertension and early glaucoma). 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…This limited agreement could also be explained by an increased variability as an early sign of glaucomatous damage in these connected sectors. Interesting in this context is a study by Cellini et al [27] They did not include SAP but compared FDT with optical coherence tomography (OCT) and pattern electroretinography (PERG) and found FDT the most sensitive and specific test for detecting early glaucomatous damage in ocular hypertensive subjects. The limited agreement in our study was found in areas where glaucoma tends to start.…”
Section: Discussionmentioning
confidence: 99%